2004
DOI: 10.1094/phyto.2004.94.8.813
|View full text |Cite
|
Sign up to set email alerts
|

Cerebroside Elicitor Confers Resistance to Fusarium Disease in Various Plant Species

Abstract: In the rice blast fungus pathosystem, cerebroside, a compound categorized as a sphingolipid, was found in our previous study to be a non-racespecific elicitor, which elicits defense responses in rice. Here we describe that cerebroside C is produced in diverse strains of Fusarium oxysporum, a common soilborne agent of wilt disease affecting a wide range of plant species. In addition, some type of cerebroside elicitor involving cerebroside A, B, or C was detected in other soilborne phytopathogens, such as Pythiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…However, cerebroside itself showed no direct in vitro antifungal activity against C. capsici (data not shown), indicating that cerebroside activates plant defense mechanisms to confer resistance against anthracnose disease. Similar observations were reported by Umemura et al (2004) where they observed cerebroside C from F. oxysporum induced the expression of PR proteins in tomato plants but had no direct antifungal activity. Furthermore, they confirmed that cerebroside isolated from various species of F. oxysporum also induced resistance against various fusarium diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, cerebroside itself showed no direct in vitro antifungal activity against C. capsici (data not shown), indicating that cerebroside activates plant defense mechanisms to confer resistance against anthracnose disease. Similar observations were reported by Umemura et al (2004) where they observed cerebroside C from F. oxysporum induced the expression of PR proteins in tomato plants but had no direct antifungal activity. Furthermore, they confirmed that cerebroside isolated from various species of F. oxysporum also induced resistance against various fusarium diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Cerebrosides were earlier extracted and purified from various fungi (Wagner and Fiegert 1969;Umemura et al 2000;Takakuwa et al 2002). Elicitor activity of purified cerebrosides was demonstrated earlier and found to induce phytoalexin and pathogenesis related (PR) protein synthesis, hypersensitive responses (HR) and resistance to infection by compatible pathogens in rice (Koga et al 1998;Umemura et al 2000 and, pearl millet (Deepak et al 2003), and tomato (Umemura et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, harpin (Wei et al, 1992;Dong et al, 1999) and fungal cerebroside (Koga et al, 1998b;Umemura et al, 2000Umemura et al, , 2004Deepak et al, 2003) prevented infection by inducing defense systems in various plants. However, the high cost involved in the practical use of such natural substances has been prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…cucumerinum , and f. sp. lactucae ), Pythium graminicola , Glomerella cingulata , and Sclerotinia cepivorum contain cerebroside elicitor (Umemura et al 2004 ). The cerebroside elicitor induced defense signaling systems and induced resistance against pathogens (Umemura et al 2004 ).…”
Section: Cerebrosides As Pampsmentioning
confidence: 99%
“…lactucae ), Pythium graminicola , Glomerella cingulata , and Sclerotinia cepivorum contain cerebroside elicitor (Umemura et al 2004 ). The cerebroside elicitor induced defense signaling systems and induced resistance against pathogens (Umemura et al 2004 ). These results suggest that cerebroside elicitors are general elicitors and considered as PAMPs (Nakashima et al 2008 ).…”
Section: Cerebrosides As Pampsmentioning
confidence: 99%